2022
DOI: 10.1021/acs.estlett.2c00186
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Polystyrene Micro- and Nanoplastics Causes Fetal Growth Restriction in Mice

Abstract: Plastics are ubiquitous and, when released into the environment, break down into smaller particles termed microplastics (MPs) and nanoplastics (NPs). These MPs and NPs can be ingested by organisms and potentially accumulate in tissues and organs. Recently, MPs were found in the placentas of healthy women, raising the concern that exposure to plastics may have an impact on pregnancy and fetal development. In this study, we investigated the effect of maternal exposure to plastics on fetal and placental growth us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 29 publications
2
35
2
Order By: Relevance
“…S1†). The significant growth restriction our group observed previously in late gestation fetuses exposed to NPs 13 did not persist at this postnatal stage.…”
Section: Resultscontrasting
confidence: 48%
See 2 more Smart Citations
“…S1†). The significant growth restriction our group observed previously in late gestation fetuses exposed to NPs 13 did not persist at this postnatal stage.…”
Section: Resultscontrasting
confidence: 48%
“…The NP concentration was selected based on our previous work. 13 The pups were not culled after birth. At P2 the pups were paw tattooed for identification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered fetal tissue macrophage function has been implicated in a number of neonatal and perinatal disorders, including hypoxic-ischemic encephalopathy (HIE), bronchopulmonary dysplasia (BPD) and necrotizing enterocolitis (NEC) [ 34 ]. In addition, several recently published studies have reported a variety of adverse effects on the fetus and progeny after oral exposure to polystyrene MNPs in pregnant mice, including metabolic disorders [ 27 , 28 ], hepatic and testicular toxicity [ 25 ], fetal growth restriction [ 24 ] and multiple developmental brain abnormalities accompanied by neurophysiological and cognitive deficits [ 23 ]. Further studies are needed to quantify the MNP concentrations and doses in the placenta and fetal organs as a function of time in a variety of exposure scenarios in order to assess the potential effects of the presence of MNPs in fetal tissues on fetal health and development, and to potentially mechanistically link the adverse effects observed in the offspring of rats exposed during pregnancy to the presence and specific locations of MNPs in fetal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exposure routes responsible for the MNPs found in human tissues are not known, and given the aforementioned findings of intestinal MNP uptake and the current estimated human MNP ingestion rate, are most likely a combination of both ingestion and inhalation. Moreover, recent studies in experimental animals found that oral exposure to MNPs during pregnancy had multiple adverse effects on pregnancy outcomes and progeny [ 23 , 24 , 25 , 26 , 27 , 28 ], suggesting potential fetal translocation of the ingested MNPs. To date, however, no study has verified the translocation of ingested MNPs to the placenta or fetal tissues, which might account for those effects.…”
Section: Introductionmentioning
confidence: 99%